Renal cell carcinoma at the time of presentation: a 5-year radiological survey at a tertiary care cancer hospital - Altaf, Muhammad Omer; Riaz, Asma; Shafqat, Mehreen; Zahra, Hamd; Iqbal, Naila; Iftikhar, Aamer (International Journal Of Community Medicine And Public Health, 2020)
Background: Renal cell carcinoma (RCC) is associated with highest mortality rates of all the genitourinary tumors with increased incidence in the past few decades. It is heterogenous tumor with several histological types. Main diagnostic approach is radiological imaging followed by histopathology. Methods: It is a retrospective study conducted at a tertiary care cancer hospital in Pakistan. We reviewed the record of all the RCC patients in terms of age, gender, radiological manifestation of tumor size, polarity, laterality, stage including nodal status, metastasis and histological type. Results: Our study included 149 patients of RCC. Mean age of presentation was 57 years with a male predominance. The most common stage of presentation was stage 3 seen in 41% patients followed by stage 1 in 37% patients. nodal metastasis was observed in around 13% patients and distant metastasis in 8% patients. Also, majority of the patient had histological subtype of clear cell CA (63%) followed by papillary CA (33%). Conclusions: Epidemiological features of renal cell CA are observed over a period of 5 years representing our population. The current trends show variation from those observed in developed countries depicting the struggle of healthcare awareness in developing countries.